A review on association and correlation of genetic variants with eating disorders and obesity - Sayed Koushik Ahamed; Md Abdul Barek; Uthpall Kumar Roy; Md Kouser; Md Sharif Reza; Afifa Binthe Mannan; Md Ashraful Alam; S. M. Naim Uddin (SpringerOpen, 2021)
Abstract Background Now, eating disorders and obesity and their correlations are danger signal in worldwide which is caused by multifactor and associated with significant mortality and morbidity. Main body Every aspect of a patient's life is influenced by eating disorders and obesity and their correlations. Due to frequent seeing of obese patients, eating disorders have been included in the review as they can sometimes be associated with obesity. However, it should be noted that most patients having eating disorder are at risk to be obese or overweight. This research explores the risk factors for the two disorders, as well as the assessment of medical complications and treatment recommendations for the disorders. In these two disorders, there is also a correlation. The essential consideration is that eating disorders are impulse-control disorders which are similar to addictive behaviors in some aspects. So it is a crying need to treat a patient with obesity and eating disorders simultaneously to ensure success. Genome-wide association studies (GWASs) have increased our knowledge of the pathophysiology of eating disorders (EDs) and obesity and their correlation. Conclusion This review enlightens on the summary of eating disorder, obesity, genotypic traits, molecular relations, interaction, correlation, and effect of eating disorder and obesity which outline potential future directions and clinical implications for patients with EDs and obesity.